2016
DOI: 10.18535/jmscr/v4i7.01
|View full text |Cite
|
Sign up to set email alerts
|

Serum Calprotectin as a Non-invasive Diagnostic Marker for Spontaneous Bacterial Peritonitis in Egyptian Cirrhotic Patients

Abstract: BACKGROUND and AIM: Delayed diagnosis of spontaneous bacterial peritonitis (SBP) is associated with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…In a different approach, serum calprotectin has been evaluated as a SBP biomarker in one study performed on 75 patients with cirrhosis. The authors observed that serum calprotectin values were significantly higher ( p < .001) in patients with SBP (61.6 ± 7.3 μg/mL) compared to noninfected AF (24.8 ± 14.8 μg/mL) and patients without ascites (24.4 ± 11.8 μg/mL), and they proposed a cut‐off value of serum calprotectin of 46 μg/mL for SBP diagnosis (AUC 0.976; p < .001; sensitivity 100%, specificity 92% and diagnostic accuracy 96%) 22 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a different approach, serum calprotectin has been evaluated as a SBP biomarker in one study performed on 75 patients with cirrhosis. The authors observed that serum calprotectin values were significantly higher ( p < .001) in patients with SBP (61.6 ± 7.3 μg/mL) compared to noninfected AF (24.8 ± 14.8 μg/mL) and patients without ascites (24.4 ± 11.8 μg/mL), and they proposed a cut‐off value of serum calprotectin of 46 μg/mL for SBP diagnosis (AUC 0.976; p < .001; sensitivity 100%, specificity 92% and diagnostic accuracy 96%) 22 …”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11][12][13][14]20,37,38 Moreover, AF calprotectin determination does not avoid the paracentesis. Finally, the limited number of observational studies that evaluated serum and faecal calprotectin [22][23][24][25] proposed a wide range of diagnostic cut-off values, hindering their implementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation